Catalytic Oxidation of Ammonia over Cerium-Modified Copper Aluminium Zinc Mixed Oxides - Sylwia Górecka (MDPI AG, 2021)
Copper-containing mixed metal oxides are one of the most promising catalysts of selective catalytic oxidation of ammonia. These materials are characterized by high catalytic efficiency; however, process selectivity to dinitrogen is still an open challenge. The set of Cu-Zn-Al-O and Ce/Cu-Zn-Al-O mixed metal oxides were tested as catalysts of selective catalytic oxidation of ammonia. At the low-temperature range, from 250 °C up to 350 °C, materials show high catalytic activity and relatively high selectivity to dinitrogen. Samples with the highest Cu loading 12 and 15 mol.% of total cation content were found to be the most active materials. Additional sample modification by wet impregnation of cerium (8 wt.%) improves catalytic efficiency, especially N2 selectivity. The comparison of catalytic tests with results of physicochemical characterization allows connecting the catalysts efficiency with the form and distribution of CuO on the samples’ surface. The bulk-like well-developed phases were associated with sample activity, while the dispersed CuO phases with dinitrogen selectivity. Material characterization included phase composition analysis (X-ray powder diffraction, UV-Vis diffuse reflectance spectroscopy), determination of textural properties (low-temperature N2 sorption, scanning electron microscopy) and sample reducibility analysis (H2 temperature-programmed reduction).